Synthesis and anаlgеsic properties of (3-allyl-4-aryl-3H-thiazol-2-ylidene)-[4-(6,7,8,9-tetrahydro-5H-[1,2,4]triazolo[4,3-a]azepin-3-yl)phenyl]amine derivatives - S. A. Demchenko; H. O. Yeromina; L. O. Perekhoda; T. A. Bukhtiarova; L. S. Bobkova; A. M. Demchenko (Фармацевтичний журнал, 2018)
In recent years, attention to itself attracted by the problem of pain treatment, which is due to a noticeable increase in patients, especially the able-bodied age. The aim of the study was to synthesize substances with potentially analgesic properties in the series of hydrobromides (3-allyl-4-aryl-3H-thiazol-2-ylidene)-[4-(6,7,8,9-tetrahydro-5H-[1,2,4]triazolo[4,3-a]azepin-3-yl)phenyl]amine and to study the effect of the synthesized compounds on the analgesic activity. The objects of the study were (3-allyl-4-aryl-3H-thiazol-2-ylidene)-[4-(6,7,8,9-tetrahydro-5H-[1,2,4]triazolo[4,3-a]azepin-3-yl)phenyl]amine derivatives, which were synthesized by boiling a thiourea with the corresponding α-haloketones in ethanol medium. Data of NMR 1H spectroscopy were used. The primary evaluation of analgesic activity was carried out on models of thermal («Hot plate») and chemical («Acetic acid cramps») stimulation. A new series of (3-allyl-4-aryl-3H-thiazol-2-ylidene)-[4-(6,7,8,9-tetrahydro-5H-[1,2,4]triazolo[4,3-a]azepin-3-yl)phenyl]amine derivatives were synthesized and their structure and purity were confirmed by NMR 1H spectroscopy. The analgesic activity of hydrobromide 3-allyl-4-phenyl-3H-thiazol-2-ylidene)-[4-(6,7,8,9-tetrahydro-5H-[1,2,4]triazolo[4,3-a]azepin-3-yl)phenyl]amine were studied to identify the «structure‒activity» relationship taking into account earlier studies. Screening for analgesic activity for the hydrobromide 3-allyl-4-phenyl-3H-thiazol-2-ylidene)-[4-(6,7,8,9-tetrahydro-5H-[1,2,4]triazolo[4,3-a]azepin-3-yl)phenyl]-amine were shown that the replacement of the ethyl radical by allyl in the third position of the thiazole ring leads to a decrease in analgesic activity. Moreover, the compound possesses a moderate analgesic effect compared to the reference drug ketorolac.